2017
DOI: 10.12693/aphyspola.132.679
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Tool Tilt Angle on 1050 Aluminum Lap Joint in Friction Stir Welding Process

Abstract: In this paper, the effect of tool tilt angle on tensile-shear failure load and weld zone properties for 1050 aluminum plates, welded by friction stir lap welding, were investigated. For this purpose, tool tilt angle was varied from 0• to 5• under the constant other parameters, such as tool geometry, tool rotation speed of 1200 rpm and tool travel speed of 30 mm/min. The tensile-shear test was employed to test the mechanical properties of the joint. Optical microscope examinations, microhardness and temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…However, in this joining technique, the process parameters play a vital role in affecting the mechanical plus the metallurgical properties of the weldment [14][15][16][17]. The higher tool rotational and the lower traverse speeds are the source of producing adequate heat for joining the base metal and those are the highest statistical influence on hardness, tensile strength, and peak temperature relative to other parameters [18][19][20]. On the other hand, the tool pin profile is governing the material movement and significantly influence the flow of plasticized material.…”
Section: Introductionmentioning
confidence: 99%
“…However, in this joining technique, the process parameters play a vital role in affecting the mechanical plus the metallurgical properties of the weldment [14][15][16][17]. The higher tool rotational and the lower traverse speeds are the source of producing adequate heat for joining the base metal and those are the highest statistical influence on hardness, tensile strength, and peak temperature relative to other parameters [18][19][20]. On the other hand, the tool pin profile is governing the material movement and significantly influence the flow of plasticized material.…”
Section: Introductionmentioning
confidence: 99%
“…The friction stir welding (FSW) process is a solid-state welding technology used in many industries recently for several reasons, such as high productivity, low defects related to melting, and high welding strength [1]. A rotational non-consumable tool penetrates inside the weld seam in the FSW process to join workpieces [2].…”
Section: Introductionmentioning
confidence: 99%
“…They studied joint configuration with pin-less and regular FSW tools. On the other hand, Barlas [1] investigated the total-contact TTA on FSW of AA1050 aluminum alloy in joint lap configuration.…”
Section: Introductionmentioning
confidence: 99%
“…Trueba Jr. et al [ 21 ] reported that the FSW tool shoulder with a raised helical design produces the best welds in terms of surface quality and mechanical properties in butt-welded aluminum 6061-T6 plates using six differently designed tools of Ti-6Al-4V material. Research has been conducted on process-parameter-related tools to reduce defects and increase the mechanical strength of FSW joints [ 27 , 28 ]. The normal force must be varied in the following four stages: tool plunge stage, dwell stage, welding stage, and tool retreating stage.…”
Section: Introductionmentioning
confidence: 99%
“…FSLW is more difficult than butt FSW. Many studies have been conducted on FSLW between Al alloys [ 11 , 13 , 28 , 34 ]. Significant research has been conducted on FSLW of Al–Mg [ 12 ], Al–Cu [ 30 , 35 ], Al–Ni [ 31 ], etc.…”
Section: Introductionmentioning
confidence: 99%